Effect of antioxidant activity of caffeic acid with cyclodextrins using ground mixture method - Ryota Shiozawa; Yutaka Inoue; Isamu Murata; Ikuo Kanamoto (Elsevier, 2018)
In the current study, we prepared a ground mixture (GM) of caffeic acid (CA) with α-cyclodextrin (αCD) and with β-cyclodextrin (βCD), and then comparatively assessed the physicochemical properties and antioxidant capacities of these GMs. Phase solubility diagrams indicated that both CA/αCD and CA/βCD formed a complex at a molar ratio of 1/1. In addition, stability constants suggested that CA was more stable inside the cavity of αCD than inside the cavity of βCD. Results of powder X-ray diffraction (PXRD) indicated that the characteristic diffraction peaks of CA and CD disappeared and a halo pattern was produced by the GMs of CA/αCD and CA/βCD (molar ratios = 1/1). Dissolution testing revealed that both GMs had a higher rate of dissolution than CA alone did. Based on the 1H-1H NOESY NMR spectra for the GM of CA/αCD, the vinylene group of the CA molecule appeared to be included from the wider to the narrower rim of the αCD ring. Based on spectra for the GM of CA/βCD, the aromatic ring of the CA molecule appeared to be included from the wider to the narrower rim of the βCD ring. This suggests that the structures of the CA inclusion complexes differed between those involving αCD rings and those involving βCD rings. Results of a DPPH radical-scavenging activity test indicated that the GM of CA/αCD had a higher antioxidant capacity than that of the GM of CA/βCD. The differences in the antioxidant capacities of the GMs of CA/αCD and CA/βCD are presumably due to differences in stability constants and structures of the inclusion complexes.